Evaluasi Penyajian Akuntansi Zakat Sebagai Sumber Pendapatan Asli Daerah (PAD) pada Baitul Mal Aceh - Cut Nila Kusumawati (Tadabbur: Jurnal Peradaban Islam, 2019)
Baitul Mal Aceh presents two different financial statements each year, which are the financial statements of SFAS No. 109 and financial statements according to Government Accounting Standards (SAP). This indicates a problem in the mechanism of disbursement and distribution of zakat funds that have been incorporated into the Original Revenue because it must follow the rules of local finance and equated with other local revenue. As for the financial report Baitul Mal Aceh as a whole has implemented a reporting system in accordance with Statement of Financial Accounting Standards No.109. However, there are still some unsuitable items, such as no amil funds, non-halal funds, no separation of non-existent funds and no reports of changes in assets under management. This should be a serious concern because with the presentation of the correct financial statements, the muzakki belief in the image of Baitul Mal Aceh will be built so as to increase the accumulation of zakat funds.